2022
DOI: 10.3390/jcdd9060192
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis in the Elderly: Challenges and Strategies

Abstract: The specific management of infective endocarditis (IE) in elderly patients is not specifically addressed in recent guidelines despite its increasing incidence and high mortality in this population. The term “elderly” corresponds to different ages in the literature, but it is defined by considerable comorbidity and heterogeneity. Cancer incidence, specifically colorectal cancer, is increased in older patients with IE and impacts its outcome. Diagnosis of IE in elderly patients is challenging due to the atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 150 publications
3
17
0
3
Order By: Relevance
“…Presently, the incidence of IE is increasing in different regions, and IE has been reported to affect up to 7 to 10 people per 100,000 person-years [ 11 ]. Several predisposing factors for the development of IE have shifted from conditions such as rheumatic heart disease or congenital heart diseases to degenerative valve disease due to the increasingly aging population [ 12 , 13 ]. In addition, the increased use of prosthesis and intra-cardiac devices are factors that predispose an individual to the development of IE [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the incidence of IE is increasing in different regions, and IE has been reported to affect up to 7 to 10 people per 100,000 person-years [ 11 ]. Several predisposing factors for the development of IE have shifted from conditions such as rheumatic heart disease or congenital heart diseases to degenerative valve disease due to the increasingly aging population [ 12 , 13 ]. In addition, the increased use of prosthesis and intra-cardiac devices are factors that predispose an individual to the development of IE [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infective endocarditis (IE) is an infection of the heart’s inner lining, known as the endocardium [ 1 ] with a high mortality and morbidity rate [ 2 , 3 ]. It is estimated that the number of incident cases has increased by 128% from 1990 to 2019, with an increased age–specific incidence rate for the population over 60 years old, with an overall five-fold increased risk of IE compared with the general population of adults which stands between 3 and 7 cases per 100 thousand patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the continuously rising incidence and moving towards the aging global population [ 4 ], studies need to focus on this specific cohort, considering that older individuals have a higher prevalence of comorbidities and present with nonspecific symptoms that make the diagnosis difficult [ 2 ]. Infective endocarditis is defined by a wide variety of nonspecific symptoms [ 3 , 5 , 6 ], with fever, chills, nausea, dyspnea, anorexia, weight loss, weakness and fatigue, headaches and shortness of breath [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the risk of endocarditis for older people is almost five times higher than that of the general population. The high frequency of undetected degenerative valve disease and the rising use of invasive procedures and implanted medical devices may be examples of such reasons [ 20 ], which may also affect the prognosis of older people with IE [ 21 ]. Several procedures require antibiotic prophylaxis for patients with cardiac conditions who are at a high risk for infective endocarditis, including maxillo-facial procedures and non-dental invasive procedures of the upper and lower gastrointestinal tract, genitourinary and gynecological procedures, and those of the upper and lower respiratory tract, including ear, nose, and throat (ENT) procedures and bronchoscopy [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%